A revised geochronology of Thurston Island, West Antarctica, and correlations along the proto-Pacific margin of Gondwana. Issue 1 (30th August 2016) - Riley, T.R.; Flowerdew, M.J.; Pankhurst, R.J.; Leat, P.T.; Millar, I.L.; Fanning, C.M.; Whitehouse, M.J.
Abstract: The continental margin of Gondwana preserves a record of long-lived magmatism from the Andean Cordillera to Australia. The crustal blocks of West Antarctica form part of this margin, with Palaeozoic–Mesozoic magmatism particularly well preserved in the Antarctic Peninsula and Marie Byrd Land. Magmatic events on the intervening Thurston Island crustal block are poorly defined, which has hindered accurate correlations along the margin. Six samples are dated here using U-Pb geochronology and cover the geological history on Thurston Island. The basement gneisses from Morgan Inlet have a protolith age of 349±2 Ma and correlate closely with the Devonian–Carboniferous magmatism of Marie Byrd Land and New Zealand. Triassic (240–220 Ma) magmatism is identified at two sites on Thurston Island, with Hf isotopes indicating magma extraction from Mesoproterozoic-age lower crust. Several sites on Thurston Island preserve rhyolitic tuffs that have been dated at 182 Ma and are likely to correlate with the successions in the Antarctic Peninsula, particularly given the pre-break-up position of the Thurston Island crustal block. Silicic volcanism was widespread in Patagonia and the Antarctic Peninsula at ~ 183 Ma forming the extensive Chon Aike Province. The most extensive episode of magmatism along the active margin took place during the mid-Cretaceous. This Cordillera 'flare-up' event of the Gondwana margin is also developed on Thurston Island with granitoid magmatism dated in the interval 110–100 Ma.